Developing adaptive digital book (ADB) in enhancing students’ numeracy literacy ability - Yerizon, Yerizon; Arnellis, Arnellis; Suherman, Suherman; Arnawa, I Made; Sa'dijah, Cholis; Anwar, Lathiful (Jurnal Infinity, 2025)
Numeracy literacy is essential for students to solve interrelated problems across various subjects. However, students' numeracy literacy skills remain low, necessitating innovative learning resources. This research focuses on designing an Adaptive Digital Book (ADB) that is claimed to be valid, practical, and effective in improving students' numeracy literacy. This study adopted a design research approach in the context of development studies, which included two main phases: the preliminary phase and the formative evaluation phase, which included self-evaluation, expert evaluation, and iterative evaluation (one-to-one, small group, and field test). Quantitative and qualitative data were gathered through assessment of numeracy literacy, interviews, and distributing questionnaires. Results showed that ADB is practical and effective in its validity as well as in meeting the requirements of students with different learning needs. The combination of multimedia elements like videos caters to visual and auditory learners, which helps improve their numeracy literacy skills.